Transient Activation of Apomixis in Sexual Neotriploids May Retain Genomically Altered States and Enhance Polyploid Establishment - Hojsgaard, Diego (Frontiers in Plant Science, 2018)
Polyploid genomes evolve and follow a series of dynamic transfigurations along with adaptation and speciation. The initial formation of a new polyploid individual within a diploid population usually involves a triploid bridge, a two-step mechanism of cell fusions between ubiquitous (reduced) and rare (unreduced) gametes. The primary fusion event creates an intermediate triploid individual with unbalanced genome sets, a situation of genomic-shock characterized by gene expression dysregulation, high dosage sensitivity, disturbed cell divisions, and physiological and reproductive attributes drastically altered. This near-sterile neotriploid must produce (even) eupolyploids through secondary fusion events to restore genome steadiness, meiotic balance and fertility required for the demographic establishment of a nascent lineage. Natural conditions locate several difficulties to polyploid establishment, including the production of highly unbalanced and rarely unreduced (euploid) gametes, frequency-dependent disadvantages (minority cytotype exclusion), severe fitness loss, and ecological competition with diploid parents. Persistence and adaptation of neopolyploids depend upon genetic and phenotypic novelty coupled to joint selective forces that preserve shock-induced genomic changes (subgenome homeolog partitioning) and drive meiotic (reproductive) stabilization and ecological diversification. Thus, polyploid establishment through triploid bridge is a feasible but not ubiquitous process that requires a number of low-probability events and singular circumstances. Yet, frequencies of polyploids suggest polyploid establishment is a pervasive process. To explain this disparity, and supported in experimental evidence I propose that situations like hybridization and ploidy-state transitions associated to genomic shock and substantial developmental alterations can transiently activate apomixis as a mechanism to halt genomic instability and cancel factors restraining neopolyploid´s sexual fertility, particularly in triploids. Apomixis skip meiosis and syngamy, and thus can freeze genomic attributes, avoid unbalanced chromosomal segregation and increase rates of unreduced euploid gametes, elude frequency-dependent reproductive disadvantages by parthenogenetic development, and increase the effective population size of the neopolyploid lineage favouring the formation rate of eupolyploids. Subsequent action of genome resilience mechanisms that alleviate transcriptomic shock and selection upon gene interactions might restore a stable meiosis and sexual fertility within few generations, as observed in synthetic polyploids. Alternatively, provided resilience mechanisms fail, the neopolyploid might retain apomixis and hold genomically and transcriptionally altered states for thousand generations.